The impact of firms’ earnings on the stock market: A study on Food Beverage and Tobacco industry in Colombo Stock Exchange - Sentheeran, K.; Anandasayanan, S. (University of Jaffna, 2020)
The research is conducted with the primary objective of identifying the impact of Earnings Per Share on Market Price Per Share, evidence from the Food, Beverage, and Tobacco companies listed on the Colombo Stock exchange over the period 2013 2019. In this study, the researchers used Earnings Per Share as independent variables and Market Price Per Share as a dependent variable, whereas Firm Size as a control variable. Descriptive Statistics, Correlation Analysis, Panel regression analysis, and Variance Inflation factors were used for the data analysis. The data were collected for 25 companies from the Food, Beverage and Tobacco industry from 2013 to 2019. Moreover, the sampling method used was Random sampling. The data were analyzed using the statistical software named Eviews 9. The findings revealed that Earnings Per Share affects the Market Price Per Share significantly and positively at a 95% confidence level, whereas Firm Size also has a positive and significant impact on Market Price Per Share
Keywords: earnings per share; firm size; market price per share